Role of the type 6 secretion system on apoptosis and macrophage polarization during Burkholderia pseudomallei infection. - Jacob L Stockton; Nittaya Khakhum; Alfredo G Torres (Public Library of Science (PLoS), 2024)
Burkholderia pseudomallei (Bpm) is the causative agent of the disease melioidosis. As a facultative intracellular pathogen, Bpm has a complex lifestyle that culminates in cell-to-cell fusion and multinucleated giant cells (MNGCs) formation. The virulence factor responsible for MNGC formation is the type 6 secretion system (T6SS), a contractile nanomachine. MNGC formation is a cell-to-cell spread strategy that allows the bacteria to avoid the extracellular immune system and our previous data highlighted cell death, apoptosis, and inflammation as pathways significantly impacted by T6SS activity. Thusly, we investigated how the T6SS influences these phenotypes within the macrophage and pulmonary models of infection. Here we report that the T6SS is responsible for exacerbating apoptotic cell death during infection in both macrophages and the lungs of infected mice. We also demonstrate that although the T6SS does not influence differential macrophage polarization, the M2 polarization observed is potentially beneficial for Bpm pathogenesis and replication. Finally, we show that the T6SS contributes to the severity of inflammatory nodule formation in the lungs, which might be potentially connected to the amount of apoptosis that is triggered by the bacteria.